2022
DOI: 10.5435/jaaos-d-22-00222
|View full text |Cite
|
Sign up to set email alerts
|

Management of Subscapularis Insufficiency After Total Shoulder Arthroplasty

Abstract: The functional success of anatomic total shoulder arthroplasty (TSA) relies heavily on the healing integrity of the subscapularis tendon. Access to the glenohumeral joint is performed through a deltopectoral approach, and takedown of the subscapularis tendon is necessary in most surgeons' hands. Although initially described as a tenotomy, lesser tuberosity osteotomy and subscapularis peel are two techniques more commonly used today. Both of these options offer good results as long as proper repair is done. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“… 8 , 14 , 15 , 16 Subscapularis re-repair with or without augmentation, pectoralis major transfer, and latissimus dorsi transfer have been described, although none reliably lead to satisfactory outcome. 17 In many cases, conversion to a reverse shoulder arthroplasty may be warranted. 8 , 14 , 15 , 16 Therefore, it is important to maximize stability of the initial subscapularis repair to avoid this potential complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 14 , 15 , 16 Subscapularis re-repair with or without augmentation, pectoralis major transfer, and latissimus dorsi transfer have been described, although none reliably lead to satisfactory outcome. 17 In many cases, conversion to a reverse shoulder arthroplasty may be warranted. 8 , 14 , 15 , 16 Therefore, it is important to maximize stability of the initial subscapularis repair to avoid this potential complication.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported on the biomechanical strength of different subscapularis repair techniques following TSA, primarily LTO, tenotomy, or peel. 3 , 17 , 26 The LTO, in particular, has demonstrated greater strength and load to failure when compared to peel or tenotomy. 27 , 28 , 29 , 30 Studies exploring the ultimate load to failure for LTO report values ranging from 301.3 to 632.3 N. 27 , 28 , 29 , 30 In the biomechanical study by Hawthorne et al., the V-shaped biceps augmented repair had a mean load to failure of 563.3N.…”
Section: Discussionmentioning
confidence: 99%
“…42 The current options for revision surgery include conservative treatment, soft-tissue repair, tendon or graft augmentation, and reverse shoulder arthroplasty (RSA). 43,44…”
Section: Management Of Osteotomy Failurementioning
confidence: 99%